ACROMEGALY – ETIOLOGY, SYMPTOMS, TREATMENT. LITERATURE REVIEW - Michał Ochwat; Katarzyna Dąbek; Aleksandra Kajtel; Anna Skowronek; Martyna Piekarska-Magiera; Adam Sielicki; Maria Ochwat; Tomasz Skowronek; Michał Oborski; Zofia Sudoł (International Journal of Innovative Technologies in Social Science, 2025)
Acromegaly is a rare endocrine disorder, typically resulting from a growth hormone (GH)-secreting pituitary adenoma. While these tumors are generally benign, they can sometimes exhibit local invasiveness or resistance to standard treatments. Clinically, the condition manifests through both distinctive physical changes and a range of systemic symptoms that may affect the cardiovascular, respiratory, metabolic, and neurological systems, and may also be associated with an increased risk of neoplastic diseases. Without timely treatment, these complications can significantly raise mortality risk, highlighting the importance of early detection. Initial screening usually includes measuring the levels of insulin-like growth factor 1 (IGF-1). Despite medical advancements, diagnosing acromegaly remains challenging, and delays in diagnosis are common, often resulting in advanced disease and severe complications. The preferred initial treatment is surgical resection of the tumor. For individuals who are ineligible for surgery or do not achieve remission postoperatively, medical therapy using somatostatin analogues is recommended. The primary therapeutic aims include normalization of IGF-1 and GH levels, reduction of tumor size, and management of associated complications.